Unveiling CD177: a key player in tumors, autoimmune diseases, and inflammatory disorders - Yang, Dongmei; Hu, Xiaobin (Frontiers in Immunology, 2025)
CD177, also referred to as human neutrophil antigen NB1 or polycythemia rubra vera-1, is a glycosylphosphatidylinositol-anchored glycoprotein with a molecular weight of approximately 58−64 kDa, predominantly expressed in neutrophils, neutrophilic myelocytes, and metamyelocytes. While extensive research has focused on the role of CD177 in neutrophils, where it is implicated in transendothelial migration, cellular viability, and bactericidal activities, its functions outside of neutrophils remain largely unexplored. Under inflammatory conditions, CD177 expression on neutrophils is significantly upregulated, facilitating their migration to sites of inflammation. CD177+ neutrophils have been shown to accumulate in inflamed tissues and modulate the release of inflammatory mediators and the formation of neutrophil extracellular traps (NETs), correlating with the severity of inflammation in conditions such as inflammatory bowel disease (IBD) and acute respiratory distress syndrome (ARDS). An imbalance in CD177+ neutrophils has been identified as a critical pathogenic mechanism in vascular inflammation, tissue necrosis, and systemic lupus erythematosus (SLE). Furthermore, CD177 expression on neutrophils, epithelial cells, and regulatory T cells in solid tumors has been associated with tumor invasion, disease stage, therapeutic responses, and patient survival in various cancers, including gastric, breast, and colorectal cancer (CRC). Nevertheless, elucidating the intricate mechanisms underlying CD177’s role in these diseases remains a significant challenge. In light of these findings, we present a comprehensive review of recent literature concerning the role of CD177 in tumors, inflammatory processes, and autoimmune diseases, with a particular focus on its mediating effects on neutrophil recruitment, transepithelial migration, and the activation of CD177-positive neutrophils, along with the functional implications of CD177 expression beyond neutrophils. A deeper understanding of CD177 may pave the way for the development of novel therapeutic strategies and the assessment of disease prognosis.